Kesalahan Makna Leksikal pada Terjemahan Teks Bahasa Indonesia ke dalam Bahasa Inggris - Ramli (FKIP, Universitas Lakidende Unaaha, 2015)
The objective of this research was to investigate the error of lexical semantic found in the translation of Indonesian text into English text done by the English Education Program students Lakidende University, Southeast Sulawesi in 2013. It was a qualitative research with a content analysis method. The data were collected using written translation test. Based on the data analysis and interpretation, the semantic error of lexis consisted of: 1) Confusion of sense relation (General term for specific one, Specific term for general one, Co-hyponym, Near-synonym) and 2) Collocation. The sources of errors were 1) Interlanguage transfer, 2) Intralanguage influence, and 3) communication strategy. There were two impacts the errors, 1) local impact and 2) global impact. As suggestion, theory and practice of translation are needed to produce quality translation.